2018
DOI: 10.3354/meps12696
|View full text |Cite
|
Sign up to set email alerts
|

Calanus finmarchicus diel and seasonal rhythmicity in relation to endogenous timing under extreme polar photoperiods

Abstract: Changing environmental conditions cause poleward distribution shifts in many marine organisms including the northern Atlantic key zooplankton species Calanus finmarchicus. The copepod has diel cycles of vertical migration and feeding, a seasonal life cycle with diapause in winter and a functioning circadian clock. Endogenous clock mechanisms control various aspects of rhythmic life and are heavily influenced by environmental light conditions. Here we explore how the extreme seasonal change in photoperiod (day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 65 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Copepods, specifically C. finmarchicus, are a dominant constituent of the zooplankton community and have been the focus of many DVM studies [2,12,23]. It has been shown that C. finmarchicus collected from a high-latitude Fjord (78°N) maintained circadian clock gene rhythmicity even under long photophases at the very end of the Midnight Sun period [24]. Our results go further, showing circadian clock gene oscillations within days of the summer solstice where daily changes in sun's altitude are at a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Copepods, specifically C. finmarchicus, are a dominant constituent of the zooplankton community and have been the focus of many DVM studies [2,12,23]. It has been shown that C. finmarchicus collected from a high-latitude Fjord (78°N) maintained circadian clock gene rhythmicity even under long photophases at the very end of the Midnight Sun period [24]. Our results go further, showing circadian clock gene oscillations within days of the summer solstice where daily changes in sun's altitude are at a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…DVM of zooplankton has also been documented in the deep sea (as a proxy for another environment without overt solar signals) yet the mechanisms of entrainment are not understood (van Haren and Compton 2013). Noteworthy is that cycling clock gene expression in C. finmarchicus, has only been demonstrated during the Polar Day, but not the Polar Night, as shown in Figure 8.2 in animals collected from Kongsfjorden (Häfker et al 2018a). Copepods in early diapause (September; for details see Chapter 5) which were collected below 200m, where light levels were probably below their visual detection limit (Båtnes et al 2015), still showed clock gene cycling.…”
Section: Circadian Clocks and Cyclesmentioning
confidence: 99%
“…As copepods typically overwinter at depth where light or other seasonal cues are unavailable or reduced, an argument is made in favour of seasonal/circannual clocks in regulating diapause timing as has been described for various insects (Meuti and Denlinger 2013). The circadian clock of C. finmarchicus remains functional during extremely long photoperiods in summer (Häfker et al 2018a), and it is likely that the same is true for the polar-adapted species C. glacialis and C. hyperboreus. Thus, the circadian clock could be used to determine the seasons based on photoperiod and the use of a critical day length in diapause initiation.…”
Section: Seasonal Clocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian clocks have been largely investigated in terrestrial species, but knowledge of marine clock systems is still scarce despite the ecological importance and complexity of marine ecosystems [17]. This is particularly true for polar ecosystems, with few studies devoted to understanding the behavioural or molecular rhythms during the polar day or night [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%